Controllable Phase Stabilities in Transition Metal Dichalcogenides through Curvature Engineering: First‐Principles Calculations and Continuum Prediction. Issue 6 (3rd May 2018) - Ouyang, Bin; Ou, Pengfei; Song, Jun
Abstract: A controllable phase transition between the semiconducting 2H phase and metallic/semimetallic T (1T, 1T′, and 1T″) isomorphs provides an effective route to tune and even switch physical and electronic properties within 2D transition metal dichalcogenides (TMDs). In this study, the feasibility of curvature engineering in manipulating the structural phase is investigated employing first‐principles density functional theory (DFT) calculations and continuum mechanics analysis. With WSe2 and MoTe2 as TMD representatives, it is found that bending deformation can not only energetically induce 2H → T (1T, 1T′, or 1T″) phase transformation, but also kinetically facilitate the phase transition by lowering transition activation barriers. Moreover, a phase stability diagram is constructed which suggests ways of achieving both uniformly 2H → T phase transition and programming printing of T phases in 2H‐TMD membranes. The theoretical results not only suggest a new feasible experimental design strategy of phase engineering, but also sheds light on novel device design with the patterning of T phases on the 2H‐TMD membrane. Abstract : A controllable phase transition between the semiconducting 2H phase and metallic/semimetallic T phases (1T, 1T′, and 1T″) MX2 isomorphs can be achieved through curvature engineering. Employing first‐principles density functional theory (DFT) calculations and continuum mechanics, phase stability diagrams under different curvature conditions are constructed. On the basis of theoretical results, multiple experimental designs of introducing curvature for flexible phase transition are proposed.